Unraveling the Effect of Aromatic Groups in Mn(I)NNN Pincer Complexes on Carbon Dioxide Activation Using Density Functional Study - Parmar, Saurabh Vinod; Avasare, Vidya; Pal, Sourav (Frontiers in Chemistry, 2021)
Carbon dioxide utilization is necessary to reduce carbon footprint and also to synthesize value-added chemicals. The transition metal pincer complexes are attractive catalysts for the hydrogenation of carbon dioxide to formic acid. There is a need to understand the factors affecting the catalytic performance of these pincer complexes through structure-activity relationship study using computational methods. It is a well-established fact that aromatic functionalities offer stability and selectivity to transition metal catalysts. However, their impact on the performance of the catalysts is lesser-known in the case of metal pincer complexes. Hence, it is necessary to investigate the catalytic performance of Mn(I)NNN pincer complexes with variably activated aromatic functionalities. In this context, fifteen catalysts are designed by placing different types of aromatic rings at the pincer carbons and two terminal nitrogen of Mn(I)NNN pincer complexes. A benzene moiety placed at C2—C3 carbons of Mn(I)NNN pincer complex with identical aromatic groups at the terminal nitrogen are found most efficient towards CO2 hydrogenation than the rest of the catalysts. On the other hand, when N,N-dimethyl aniline is placed at C2—C3 carbons of Mn(I)NNN pincer complexes then the catalytic performance is significantly decreased. Thus, the present study unravels the impact of aromatic groups in Mn(I)NNN pincer complexes towards the catalytic hydrogenation of carbon dioxide.